Avaliação de fatores preditores para a sonolência excessiva residual em pacientes com apneia obstrutiva do sono em tratamento com CPAP - Otuyama, Leonardo Jun [UNIFESP] (2016)
Residual excessive sleepiness (RES) is associated with reduced quality of life and increased risk for accidents in CPAP-treated obstructive sleep apnea patients. We designed a prospective study to identify polysomnographic, clinical and demographic risk factors for RES incidence. Out of 218 consecutive patients, we included 202 with apnea/hypopnea index >20. At baseline, all participants underwent clinical interview, Epworth sleepiness scale and baseline and CPAP-titration polysomnographies. After one-year of CPAP treatment, sleepiness and treatment compliance were assessed. Multiple sleep latency test was used to rule out narcolepsy, and a further increase in CPAP pressure was applied to rule out undertitration if Epworth score >10. Participants were assigned to two groups [RES(+); RES(-)] according to presence of RES. We compared baseline characteristics between those groups and a regression model including 11 variables was conducted to predict RES. The analysis included 113 CPAP-compliant participants. Before treatment, RES(+) (12%) had significantly shorter sleep onset latency, lower N1% and higher Epworth score than RES(-). Regression analysis identified baseline Epworth score as a predictor of RES after treatment (b=0.19, 95%CI 0.06-0.33). In conclusion, we found that having higher baseline excessive sleepiness may be a risk factor for RES, suggesting that these patients need a sleepiness-specific treatment along with CPAP.